Teaching children with autism spectrum disorder and other developmental disabilities to perform multistep requesting using an iPad. (3rd April 2017) - Alzrayer, Nouf M.; Banda, Devender R.; Koul, Rajinder
Abstract: Many children with autism spectrum disorders (ASD) and/or developmental disabilities are unable to meet their daily communication needs with speech alone. These individuals are considered potential candidates for speech-generating devices (SGDs) and mobile technologies with AAC-specific applications. The purpose of this study was to determine the effectiveness of systematic instruction on teaching multistep requesting skills using an iPad loaded with Proloquo2Go to children with ASD and other developmental disabilities. The participants in this study were four children between the ages of 8 and 10 years diagnosed with ASD and/or other developmental disabilities. The results indicated that for these participants, the intervention was effective in increasing multistep requesting using the iPad. All participants were successful to varying degrees in navigating across pages and combining symbols to request preferred items. Additionally, the participants demonstrated generalization of newly acquired skills by requesting different preferred items and activities during the generalization probes. Results are discussed and implications for research and practice are presented.